Latar Belakang Hidup Dan Pendidikan Rabinik Paulus Dalam Kaitannya Dengan Perjumpaannya Dengan Kristus - Robinson Rimun (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2019)
Paul's historical aspects relating to his background in life and education since childhood have had a great impact on Paul's theological mindset and concepts before and after his conversion. Pauline scholars gave much attention to early education in Tarsus and in Jerusalem which later made Saul a respected rabbi Pharisee. The Apostle Paul, formerly known as Saul of Tarsus, grew up in a Hellenistic environment and used Greek, which was commonly used in the Roman empire. His Hellenistic and Jewish background of life and education became the main emphasis in this article. Saul was radically changed by God after his conversion on the road to Damascus (Acts 9:4); however, this article focuses on Paul’s childhood and education in detail in order to understand the Hellenistic and Judaic influence in his theology